THE IMPACT OF INDONESIAN MEDICAL DOCTORS NATIONAL COMPETENCY EXAMINATION (IMDNCE) TOWARDS LEARNING AND CLINICAL PRACTICES: A QUALITATIVE STUDY ON THE INTERNSHIP DOCTORS’ PERSPECTIVES - Lukas Daniel Leatemia; Yoga Pamungkas Susani; Detty Iryani; Fundhy Sinar Ikrar Prihatanto; Hemma Yulfi; Rilani Riskiyana; Gandes Retno Rahayu (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2022)
Background: The implementation of the national licensing examination for medical doctors is expected to have a broad impact on doctors and society. Indonesian Medical Doctor National Competency Examination (IMDNCE; Indonesian: Uji Kompetensi Mahasiswa Program Profesi Dokter or UKMPPD) as an ‘exit exam’ in the medical education process may significantly impact learning and clinical practices. The study’s objective was to explore the impact of IMDNCE on both the learning and clinical practices of doctors.Methods: The study subjects were internship doctors who had passed the IMDNCE. Participants were recruited by purposive sampling based on the ownership status of the institution (state/private) and the accreditation of respective medical schools and participants’ gender. The study participants consisted of 41 internship doctors working in 6 regions from 33 different medical schools out of 75 medical faculties in Indonesia.Results: IMDNCE has a positive influence on learning and clinical practice. The IMDNCE process emphasizes standard competencies that must be mastered and patient management process with current evidence that is not always achieved during clinical education, increasing clinical knowledge and skills, and increasing awareness of professional development. IMDNCE also has very well affected in the development of self-confidence and a sense of responsibility which are essential in clinical practice. In addition to psychological influences, IMDNCE improves competence in clinical skills and promotes good medical practice.